2016
DOI: 10.1016/j.tranon.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Focal Adhesion Kinase Suppresses the Malignant Phenotype in Rhabdomyosarcoma Cells

Abstract: Despite the tremendous advances in the treatment of childhood solid tumors, rhabdomyosarcoma (RMS) continues to provide a therapeutic challenge. Children with metastatic or relapsed disease have a disease-free survival rate under 30%. Focal adhesion kinase (FAK) is a nonreceptor tyrosine kinase that is important in many facets of tumorigenesis. Signaling pathways both upstream and downstream to FAK have been found to be important in sarcoma tumorigenesis, leading us to hypothesize that FAK would be present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
4
15
0
Order By: Relevance
“…In accordance with this prominent role of FAK, we found that its expression in sarcoma patient samples significantly correlated with tumor grade and aggressiveness. These findings about the role of FAK in invasion and metastasis are in line with previous studies in other sarcoma subtypes [31] , [32] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with this prominent role of FAK, we found that its expression in sarcoma patient samples significantly correlated with tumor grade and aggressiveness. These findings about the role of FAK in invasion and metastasis are in line with previous studies in other sarcoma subtypes [31] , [32] .…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, the expression and activation status of FAK have been related with decreased overall survival and metastasis-free survival and increased migration in osteosarcoma [31] . In addition, FAK inhibition resulted in decreased invasion, migration, and tumor growth in rhabdomyosarcoma [32] . Here, we used our previously developed MRCLS model [33] , [34] , as well as an MRCLS cell line, to thoroughly characterize the mechanisms used by FUS-CHOP to promote cell invasion.…”
Section: Introductionmentioning
confidence: 96%
“…With increasing concentrations, these two drugs decreased total FAK expression in both PDXs and these findings have been noted in other cancer types such as pancreatic cancer [40, 41]. Prior pediatric studies utilizing PF and Y15 demonstrated decreased cell viability and proliferation with an increase in apoptotic markers [19, 21, 28, 35, 42]. Our results demonstrated similar findings with significantly decreased cell survival and proliferation with both PF and Y15 in the primary and metastatic PDXs.…”
Section: Discussionsupporting
confidence: 87%
“…Ectopic sarcoma xenograft models were previously established elsewhere by subcutaneous injection of SJCRH30 [ 57 ], SK-UT-1 [ 58 ], MES-SA [ 58 ], MES-SA/Dx5 [ 59 ], A673 [ 60 ] or SYO-1 [ 61 ] cells. Cells were resuspended in Hank's Balanced Salt Solution (Thermo Fisher Scientific, Waltham, MA) and subcutaneously transplanted into the back of nude mice.…”
Section: Methodsmentioning
confidence: 99%